1994
DOI: 10.1177/156482659401500303
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profile of the Population in a Food-For-Work Project Area: A Case Study from Samburu District, Kenya

Abstract: The nutrition status of Samburu tribesmen of northern Kenya and the potential nutritional effects of a food-for-work programme were assessed by anthropometric and dietary surveys over a period of five weeks. The investigations were carried out at four input localities, where the programme had provided a daily average of 173 kcal and 5 g protein per capita over the preceding year, and a fifth control area. Compared with Kenya as a whole, the Samburu community showed an unexpectedly high prevalence of wasting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In most studies, only the absence/presence of food-aid transfers is indicated, and only anecdotal data on food aid amounts per recipient and their income value are provided (see Table A1). In certain parts of the study area, more than 40 per cent of the population receive some food aid during the year (GFA, 1993;Kielmann et al, 1994) and during the most recent drought (1999±2000) the number was much higher (see United Nations, 2000). As Table A1 demonstrates, more than 70 per cent of studies indicate the presence of food aid, with data more readily available for Kenyan than Ethiopian sites.…”
Section: Comparative Analysis Of Variablesmentioning
confidence: 99%
“…In most studies, only the absence/presence of food-aid transfers is indicated, and only anecdotal data on food aid amounts per recipient and their income value are provided (see Table A1). In certain parts of the study area, more than 40 per cent of the population receive some food aid during the year (GFA, 1993;Kielmann et al, 1994) and during the most recent drought (1999±2000) the number was much higher (see United Nations, 2000). As Table A1 demonstrates, more than 70 per cent of studies indicate the presence of food aid, with data more readily available for Kenyan than Ethiopian sites.…”
Section: Comparative Analysis Of Variablesmentioning
confidence: 99%
“…The identity of women continues to be defined through their role as food providers even as they become dependent on a primarily male resource-cash-to fulfill that role (see also Straight 1997). Food scarcity poses problems for elders (e.g., Holtzman 2001;Kielmann et al 1994), as well, who are expected to show restraint in eating and from whom the processes of food allocation are often hidden.…”
Section: Consumption and Eatingmentioning
confidence: 99%
“…This is particularly the case within contexts in which resources are inadequate to meet basic nutritional needs -a situation in which elders may be disadvantaged vis-à-vis women because of their lesser role in food distribution, while lacking the freedom of moran to seek their share elsewhere. Indeed, nutritional data (though inconclusive due to methodological difficulties in their collection) indicate higher levels of undernutrition among elders as compared to both women and moran (Kielmann et al 1994). Comparison with the neighbouring Turkana shows that men, though receiving greater amounts of prestige foods (presumably due to their position of authority) are not better off nutritionally, and actually lose relatively more body mass than women in times of drought, and recover it more slowly in times of plenty (Galvin 1985).…”
Section: 'Gastropolitics' and The Gerontocracymentioning
confidence: 99%